Patterns of youth cigarette experimentation and onset of habitual smoking - Friedman, AS; Buckell, J; Sindelar, JL (Elsevier, 2019)
Introduction Although research suggests that youth e-cigarette experimentation is associated with later combustible cigarette experimentation, it is unclear how this relates to habitual smoking. This study assesses how minors’ patterns of combustible cigarette and e-cigarette experimentation relate to habitual smoking at ages 18–21 years.